Special Autonomy Policy of Papua Province - Rusdianto Abu (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Papua Province has a special regulation that regulates the sustainability of the wheels of government in Papua Province, namely the Special Autonomy of Papua Province. Law number 21 of 2001 concerning Special Autonomy of Papua which has been amended into Law Number 2 of 2021 concerning the Second Amendment to Law Number 21 of 2001 concerning Special Autonomy for Papua Province. Provide traffic for Papua Province to carry out special autonomy. Referring to this explanation, the author is interested in being able to conduct a study on the Special Autonomy Policy of Papua Province. This research uses Qualitative techniques with Snow Ball Technique research informants. The conclusions of the research results are as follows: Special autonomy policy has not been implemented effectively. Limitations of policy implementation in satisfying (1) the interests of affected parties, (2) the types of benefits received, (3) the expected rate of change, (4) the location of decision making, (5) program implementers, and (6) resource commitments, theoretically, indicate a lack of intended optimality. In addition, deficiencies were identified in (7) estimating player strength; (8) foresee the interests of actors; (2009) predicted the tactics of the actors; 10) foresee regime and institutional features; (11) estimating compliance; and (12) estimate the response. In practice, the implementation of special autonomy policies has improved the Human Development Index of Papua Province. There are three types of obstacles that hinder Papua Province's efforts in implementing the special autonomy policy and improving the Human Development Index: structural, cultural, and conditional. Structural constraints are caused by the power dynamics of the political elite as well as the work culture, leadership, and mindset of the bureaucratic apparatus, most of which are KKKN. Cultural limitations are a result of the scarcity of human, social, and traditional resources that have been deeply embedded in the daily lives of indigenous Papuans. Conditional restrictions are restrictions caused by poverty caused by limitations, community decline, and remote locations. resources with an individual focus